Peran Strategi HRM dalam Meningkatkan Employee Engagement dan Retensi Karyawan Pada PT. ABC [The Role of HRM Strategy in Increasing Employee Engagement and Employee Retention at PT. ABC] - Kho, Ardi; Teuku Alif Ananda; Christina Michelle; Savira Alifa; Yustika Rusnanda (Universitas Pelita Harapan, 2025)
This study aims to analyze the role of Human Resources Management (HRM) strategies in improving employee engagement and retention at Sport7 and ABC Sport, using a case study of the Sport program. A quantitative approach was used through the distribution of questionnaires to 65 respondents using a purposive sampling technique. The results showed that Sport7 employees had high levels of work engagement across the dimensions of vigor, dedication, and absorption, while ABC Sport employees demonstrated low levels across all dimensions. These findings indicate that effective HRM strategies, such as a supportive work environment, reward systems, and coaching programs, have a positive impact on employee motivation and loyalty. Conversely, the absence of such strategies contributes to low engagement and retention. This study provides important implications for organizations to evaluate and strengthen HRM strategies to create a productive and sustainable workforce. Abstrak Bahasa Indonesia: Penelitian ini bertujuan untuk menganalisis peran strategi Human Resources Management (HRM) dalam meningkatkan employee engagement dan retensi karyawan pada Sport7 dan ABC Sport, dengan studi kasus pada program Sport. Pendekatan kuantitatif digunakan melalui penyebaran kuesioner kepada 65 responden dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa karyawan Sport7 memiliki tingkat keterlibatan kerja yang tinggi pada dimensi vigor, dedication, dan absorption, sementara karyawan ABC Sport menunjukkan tingkat yang rendah pada seluruh dimensi tersebut. Temuan ini mengindikasikan bahwa strategi HRM yang efektif, seperti lingkungan kerja yang suportif, sistem penghargaan, dan program coaching memiliki dampak positif terhadap motivasi dan loyalitas karyawan. Sebaliknya, absennya strategi tersebut berkontribusi terhadap rendahnya engagement dan retensi. Penelitian ini memberikan implikasi penting bagi organisasi untuk mengevaluasi dan memperkuat strategi HRM demi menciptakan tenaga kerja yang produktif dan berkelanjutan.